PERSUASÃO E EMOÇÃO:UMA ANÁLISE MULTISSEMIÓTICA DA CONSTRUÇÃO DO APELO EMOCIONAL EM UMA CAMPANHA DE INCENTIVO AO ISOLAMENTO SOCIAL (Muitas Vozes, 2022)
The present paper deals with the relevance of combining the theories of Linguistic Politeness (BROWN; LEVINSON, 1987) and Visual Design Grammar (KRESS; VAN LEEUWEN, 2006) for the analysis of multisemiotic texts. To this end, we develop an interpretive-qualitative analysis of an awareness campaign about social isolation promoted in 2020 by the Cancer Hospital located on Mato Grosso, with the aim of verifying how the producers of this piece employ visual and verbal resources as strategies of emotional appeal seeking the persuasion and adherence of the reader. The results obtained from the analysis of the advertising piece show that the advertisers use several strategies to convince the reader to do what is asked of him, either through the verbal text or the non-verbal resources used. The conclusions suggest the importance of finding ways to enable an integrated analysis of all the resources employed in the construction of the meanings of a textual production.